An experiment of scalable video security solution using H.264/AVC and advanced encryption standard (AES): Selective cryptography - Abomhara, Mohamed; Khalifa, Othman Omran; Zaidan , A. A.; Zaidan , B. B.; Zakaria, Omar; Gani, Abdullah (Academic Journals, 2011)
This paper presents an efficient and effective framework for the design and development of enhanced selective video encryption scheme for H.264/AVC based on advanced encryption standard (AES). Due to the importance of maintaining the security of information that is publicly displayed, many approaches have been implemented to provide security for information dissemination over the networks. These include encryption, authentication, and digital signatures. For video, the method has been adopted to protect unwanted interception and viewing of any video while in transmission over the networks. In this paper, we design a new selective video encryption based on H.264/AVC and AES. In this proposed scheme, instead of encrypting the entire video stream bit by bit, only the I-frames bitstreams are encrypted. This method took into consideration the good features of selective encryption algorithms with regard to computational complexity, and data compression performance. The proposed scheme was tested in the simulated environment using different video sequences. The experimental results show that the proposed method provides adequate security to video streams. It has no effect on compression ratio and does not reduce the original video compression efficiency. Moreover, it is a suitable technique for secure H.264 bitstreams that require transmission or storage in un-trusted intermediate devices. Ø¢Â©2011 Academic Journals.